Effect of anti-vascular endothelial growth factor antibody during early fetal development in rats. (November 2014) - Kaygusuz, Ikbal; Eser, Ayla; Inegol Gumus, Ilknur; Kosus, Aydin; Yenidunya, Sibel; Namuslu, Mehmet; Kafali, Hasan
Abstract Objective: To examine the effect of anti-vascular endothelial growth factor (VEGF) antibody Bevacizumab during early fetal development in rats. Methods: Presumed-pregnant rats received single intraperitoneal injection of Bevacizumab (0–20 mg/kg) on gestational day (GD) 3, 7, and 14 (n = 2 rats/group). After Study 1 (dose range finding study), Study 2 performed with intraperitoneal 20 mg/kg bevacizumab or saline on GD 7 (n = 6 rats/group including the Study 1). Blood samples were collected 3 and 7 d after the injection. Uterus and ovarian tissues were obtained 7 d after the injection. Number of gestational sacs (GS), size of GS and fetus, serum rat β chorionic gonadotropin (β-CG), and platelet endothelial cell adhesion molecule (PECAM) for immunohistochemical assessment of angiogenesis were evaluated. Results: Number of GS, size of GS, and fetus were lower in the study group than the control group. Serum rat β-CG levels were significantly increased in the control group and significantly decreased in the study group. Staining densities for PECAM in vascular structures in both corpus luteum and placenta were lower in the study group than the control group. Conclusion: Anti-VEGF antibody has an inhibitory effect on pregnancy development and caused litter death.